Miles Lewis #2 : Whiz Kid - Kelly Starling Lyons (Penguin Workshop, 2022)
Miles Lewis has been waiting forever to be part of a city-wide science competition. Now his dream is finally coming true, and he's even part of an all-star team that includes his good friend, Jada. He should be in his element, so he can't seem to figure out why he feels like the weak link instead. While everyone else is rocking the project, Miles keeps messing up, and the team bickers and loses momentum. Miles is filled with self-doubt, and he has to wonder: Is he really a whiz at science, or is he actually a flop?
Keywords: Realistic Fiction -- Realistic Fiction